1975
DOI: 10.1111/j.1432-1033.1975.tb02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Role and Mode of Operation of the Very-Lysine-Rich Histone H1 (F1) in Eukaryote Chromatin. Histone H1 in Chromatin and in H1 . DNA Complexes

Abstract: The nuclear magnetic resonance (NMR) spectrum of chromatin at ionic strengths below about 0.5 M may be attributed solely to its histone H1 component. The effect of various ions and urea on the complex has been investigated using NMR and confirm that the contraction of the complex on increase of ionic strength is largely due to electrostatic interactions. A detailed study of the H1 . DNA complex has also been undertaken. The behaviour of H1 in the two cases is virtually identical, implying that in chromatin the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
1

Year Published

1976
1976
1979
1979

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 12 publications
4
25
1
Order By: Relevance
“…It is noteworthy that throughout the salt range over which the protein is bound to DNA (z 0-0.4 M NaCl) a welldefined protein spectrum is observed, suggesting that there is a portion of the molecule that is entirely free even under these conditions. This is in contrast to what is observed with histones, in particular H1 [15]. The presence of a section of protein 1 that always remains free from DNA could be related to the observation that DNA binds up to 10 times its own weight of high-mobility-group protein [3,4] and yet remains soluble.…”
Section: Interactions With D N Acontrasting
confidence: 46%
See 1 more Smart Citation
“…It is noteworthy that throughout the salt range over which the protein is bound to DNA (z 0-0.4 M NaCl) a welldefined protein spectrum is observed, suggesting that there is a portion of the molecule that is entirely free even under these conditions. This is in contrast to what is observed with histones, in particular H1 [15]. The presence of a section of protein 1 that always remains free from DNA could be related to the observation that DNA binds up to 10 times its own weight of high-mobility-group protein [3,4] and yet remains soluble.…”
Section: Interactions With D N Acontrasting
confidence: 46%
“…The NMR spectrum of protein 1 was therefore observed in the presence of DNA at various ionic strengths at neutral pH. Previous experiments of this nature with histones have established that not only is the spectrum of the DNA so broad as to be unobservable under the normal spectrometer conditions, but so also is the spectrum of protein that is bound to the DNA [15]. Fig.8 shows the results for protein 1 together with the spectrum of free protein at the same ionic strengths and pH for comparison.…”
Section: Interactions With D N Amentioning
confidence: 99%
“…It is well known that these concentrations of mono-or divalent cations lead to a condensation of chromatin which is mediated by histone H1 [54]. Therefore we investigated the effect of removing histone H1 from chromatin on the degradation by DNase I1 in the presence and absence of divalent cations.…”
Section: Efrhct Of the Removal Of Histone Hi On The Digestion Of Chromentioning
confidence: 99%
“…Interest in this histone fraction has been stimulated by the observation that they are apparently not, as are the other histones, involved in the basic subunit structure of the chromosome [2], but may be involved in its higher order structure. It is now quite clear that the H1 histones are the active agents in salt-induced chromatin condensation [3], and there is good evidence that they are also involved in mitotic chromosome condensation in vivo [4].…”
mentioning
confidence: 99%
“…Interest in this histone fraction has been stimulated by the observation that they are apparently not, as are the other histones, involved in the basic subunit structure of the chromosome [2], but may be involved in its higher order structure. It is now quite clear that the H1 histones are the active agents in salt-induced chromatin condensation [3], and there is good evidence that they are also involved in mitotic chromosomePhysical studies on the H1 molecule in solution have shown that under physiological conditions of pH and ionic strength the molecule folds into a globular structure [S], and there is evidence that this structure does not involve the whole molecule. It would seem reasonable that this globular structure reflects some state of the H1 histone in chromatin, and we have invested some effort in attempts to isolate the globular portion of the molecule by chemical and enzymic cleavage.…”
mentioning
confidence: 99%